SISTEM PAKAR DIAGNOSA PENYAKIT JANTUNG DAN PEMBULUH DARAH MENGGUNAKAN METODE FORWARD CHAINING - Dian Permata Sari; Melissa Triandini; Budi Harto; Mike Febri Mayang Sari (Smart Education, 2026)
Abstract: In Indonesia, heart disease remains the leading cause of death. According to data from the Health Department, 75% of deaths in Indonesia are caused by non-communicable diseases (NCDs), which can be prevented by maintaining a healthy diet and early detection of symptoms. To address this issue, technology capable of emulating human thinking in the form of artificial intelligence, namely expert systems, is needed. Expert systems will provide initial information regarding a patient's condition based on the symptoms or complaints experienced by the patient. Forward chaining is one method that can be used in expert systems. This system searches for data, creates rules, and applies reasoning. The knowledge base is obtained from medical experts, literature, and observational results, then processed using a programming language. The results of this study indicate that an expert system for diagnosing and providing treatment using the forward chaining method has been successfully built, and the application can be used to assist the general public in making diagnoses by inputting the symptoms experienced, and the expert system will provide diagnostic results and provide treatment. Keywords: Expert System, Forward Chaining, Heart Disease, Artificial Intelligence, Diagnosis Abstrak: Di Indonesia penyakit jantung masih menjadi penyebab kematian tertinggi. Data dari dinas kesehatan 75% kematian di Indonesia disebabkan oleh penyakit tidak menular (PTM), yang dapat dicegah dengan mengatur pola makan yang sehat serta mengetahui secara dini gejala dari penyakit ini. Untuk menjawab permasalah tersebut maka diperlukan suatu teknologi yang mampu mengadopsi cara berfikir manusia dalam bentuk teknologi kecerdasan buatan, yaitu system pakar. System pakar akan memberikan informasi awal terkait kondisi pasien berdasarkan dengan gejala atau keluhan yang dirasakan pasien. Forward chaining merupakan salah satu metode yang dapat digunakan dalam system pakar. System ini mencari data, membuat aturan dan menerapkan penalaran. Basis pengetahuan diperoleh dari pakar medis, literatur, dan hasil observasi, kemudian diolah menggunakan bahasa pemrograman. Hasil penelitian ini menunjukkan sistem pakar untuk mendiagnosa dan memberikan penanganan menggunakan metode forward chaining ini berhasil dibangun dan aplikasi dapat digunakan untuk membantu masyarakat umum mendiagnosa dengan memasukkan gejala yang dirasakan dan sistem pakar akan memberikan hasil diagnosa serta memberikan penanganannya. Kata Kunci: System Pakar, Forward Chaining, Penyakit Jantung, Artificial Intelligence,Diagnosa